Autonomic and cognitive function response to normobaric hyperoxia exposure in healthy subjects. Preliminary study - Kujawski, S; Słomko, J; Morten, KJ; Murovska, M; Buszko, K; Newton, JL; Zalewski, P (MDPI, 2020)
Background and objective: This is the first study to investigate the effect of high-flow oxygen therapy, using a normobaric chamber on cognitive, biochemical (oxidative stress parameters and the level of neurotrophins), cardiovascular and autonomic functioning.